HUKUM CAMBUK & OPINI PUBLIK: ANALISIS TEMATIK TANGGAPAN NETIZEN TERHADAP BERITA PELANGGARAN SYARIAT ISLAM DI AKUN FACEBOOK MEDIA MASSA - Ainal Fitri; Muhammad Haekal (SOURCE : Jurnal Ilmu Komunikasi, 2021)
This qualitative descriptive research studied the public narratives regarding the caning execution news on Serambinews.com's Facebook fan page. Apart from that, this research also investigated the relationship between Facebook users' discussion against public policy (Sharia law) and the existence of Serambinews.com as the news media. This research used the five most commented news links from January 2018 to December 2020 as the data. This data was analyzed using Thematic Analysis and studied using the concept of Public Opinion. The results showed that the public often discussed four dominant themes, including two topics that exhibited negative nuances, such as proposing extreme punishment and defamation against the convicts. These themes were a reflection of the growing public opinion regarding the caning in Aceh. Negative public opinion had the potential to form a consensus and affected public policy regarding Sharia law. But on the other hand, despite the domination of negative public opinion, the researcher argued that Serambinews.com gained economic benefits from this practice.